THE EFFECT OF GREEN MARKETING AND GAMIFICATION ON PURCHASE DECISIONS WITH BRAND IMAGE AS A MODERATING VARIABLE (CASE STUDY ON FORE COFFEE PRODUCTS IN PEKANBARU) - Rajunaini Hulda; Tengku Firli Musfar; Agnes Alvionita3 (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study seeks to examine the influence of Green Marketing and Gamification on Purchase Decision with Brand Image as a moderating variable among Fore Coffee consumers in Pekanbaru. The research employed a quantitative approach using a survey method, with data collected from 140 respondents who had previously purchased Fore Coffee products. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. The results indicate that both Green Marketing and Gamification have a positive and significant effect on Purchase Decision. However, Brand Image does not significantly moderate the relationship between Green Marketing or Gamification and Purchase Decision. This suggests that although sustainable marketing strategies and Gamification elements can drive consumer Purchase Decisions, the Brand Image of Fore Coffee is not yet strong enough to enhance these effects. This research provides practical implications for companies in designing more effective marketing strategies, while also highlighting the importance of strengthening Brand Image to support the success of marketing campaigns